2010
DOI: 10.1093/ndt/gfq549
|View full text |Cite
|
Sign up to set email alerts
|

C4d staining in post-reperfusion renal biopsy is not useful for the early detection of antibody-mediated rejection when CDC crossmatching is negative

Abstract: These data show that C4d staining in 1-h Bx is, in general, not useful for the early detection of AMR when CDC-XM is negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…The authors concluded that C4d staining in peritubular capillaries might be seen as early as one hour after transplantation in some recipients with low levels of DSA 20 . In a more recent study, 14 patients with antibody-mediated rejection had negative C4d staining in post-reperfusion biopsies 21 . It is likely that these patients were not as sensitized as those in our or the Haas study.…”
Section: Discussionmentioning
confidence: 93%
“…The authors concluded that C4d staining in peritubular capillaries might be seen as early as one hour after transplantation in some recipients with low levels of DSA 20 . In a more recent study, 14 patients with antibody-mediated rejection had negative C4d staining in post-reperfusion biopsies 21 . It is likely that these patients were not as sensitized as those in our or the Haas study.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to a standard histopathology core, another core was collected for gene expression studies. 25 Diagnosis was done first by a local pathologist and the reports were reviewed by CV and DRS to make final phenotypic assignments (discovery) and by a site-specific local pathologist and a central TGCG pathologist (validation). 24 C4d staining was performed by IF.…”
Section: Histological Analysismentioning
confidence: 99%
“…24 C4d staining was performed by IF. 25 Diagnosis was done first by a local pathologist and the reports were reviewed by CV and DRS to make final phenotypic assignments (discovery) and by a site-specific local pathologist and a central TGCG pathologist (validation). Both assessments (local and central) were performed blinded to the microarray results.…”
Section: Histological Analysismentioning
confidence: 99%
“…For example, C4d staining in post-reperfusion renal biopsy is not useful for the early detection of AMR when CDC crossmatching is negative (David-Neto et al, 2010). In ABO-incompatible transplant cases, AMR is difficult to be diagnosed by C4d analysis.…”
Section: Suspicious For Amrmentioning
confidence: 99%